2017
DOI: 10.1136/bmjoq-2017-000182
|View full text |Cite
|
Sign up to set email alerts
|

Improving transitions of care: a resident-driven approach to address delays in patient care during the direct admission process

Abstract: Background The direct admission process is a complex system that can be aggravated by inherent gaps in communication leading to inefficient continuity of care and patient safety issues. Bypassing the emergency room, triage is often associated with long periods of unmonitored observation and significant delays in patient assessment. We identified significant communication gaps, delays in placement of admission orders and patient assessment during the direct admission process at our institution. To address this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 1 publication
0
12
2
Order By: Relevance
“…Statistical analysis showed that this decrease in mean time was statistically significant for PDSA 2. Although the absolute change in mean time to orders placed is less than that found by Goolsarran et al 3 (100 minutes compared with 27 minutes), this difference is likely due to a markedly different baseline (153 minutes compared with 84.8 minutes). The final mean time to orders placed is similar and within our stated objective.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Statistical analysis showed that this decrease in mean time was statistically significant for PDSA 2. Although the absolute change in mean time to orders placed is less than that found by Goolsarran et al 3 (100 minutes compared with 27 minutes), this difference is likely due to a markedly different baseline (153 minutes compared with 84.8 minutes). The final mean time to orders placed is similar and within our stated objective.…”
Section: Discussioncontrasting
confidence: 60%
“…The final mean time to orders placed is similar and within our stated objective. 3 The percentage of patients with orders placed within 60 minutes or less improved in the intervention groups but was not statistically significant in either PDSA cycle, which was most likely secondary to low patient numbers.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Directly admitting a stable patient to the hospital is appropriate because it bypasses an often-overcrowded ED and can positively impact patient throughput. 7 The transfer of relevant clinical information is a crucial step in ensuring continuity of safe, timely, and adequate patient care. 2 Miscommunication or lack of pertinent patient information is a leading cause of medical errors.…”
Section: Purposementioning
confidence: 99%